PENDIDIKAN PERDAMAIAN SEBAGAI PANGGILAN PROFETIS GEREJA DI TENGAH KRISIS KEMANUSIAAN GLOBAL - Siahaan, Wilson Afandi; Siagian, Riris Johanna (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The current global humanitarian crisis, encompassing war, ethnic violence, human rights violations, economic inequality, and environmental degradation, presents urgent moral and spiritual challenges for the church as the body of Christ. In this context, the church is called to fulfill its prophetic role, proclaiming justice, truth, and peace, while serving as a witness of God’s reconciling love in the world. Peace is understood not merely as the absence of conflict, but as the restoration of relationships between humans, God, fellow humans, and creation, as implied in the concepts of syalom and eirene. The church’s prophetic calling demands moral courage to oppose injustice, discrimination, and practices that undermine human dignity, while offering practical solutions grounded in love, justice, and reconciliation. In practice, church strategies include peace education, social advocacy, reconciliation, interfaith and cross-sector collaboration, as well as utilizing technology to disseminate messages of peace. This theological and prophetic dimension emphasizes that the church’s calling is holistic spiritual, social, and structural so that peace becomes a tangible experience for individuals, communities, and society at large. Thus, a church that lives out its prophetic calling is not only a teacher of God’s truth but also a social transformation agent relevant to global dynamics. This study employs a qualitative approach through library research, with descriptive analytical analysis of theological literature, church documents, and academic writings on peace theology. This method enables the identification of key ideas, interpretation of theological meanings, and translation of the church’s prophetic peace concepts into contemporary social contexts